Adapting the low-cost pre-disinfection column PREDICO for simultaneous softening and disinfection of pore water. (January 2022) - Isidro, J.; Sáez, C.; Llanos, J.; Lobato, J.; Cañizares, P.; Matthée, T.; Rodrigo, M.A.
Abstract: In previous works, a low-cost predisinfection column that combined coagulation-flocculation and GAC filtration was proposed for combination with electrodisinfection in the successful treatment of highly faecal polluted surface water. In this work, this column is adapted for the treatment of pore water by transforming the coagulation chamber into a chemical reactor with lime and replacing the GAC of the filter with ion exchange resins. This adapted system can soften water, remove nitrate and condition water for very efficient electrochemical disinfection, where 4 logs and 3 logs in the removal of E. coli and P. aeruginosa, respectively, were reached using commercial electrochemical cells, i.e., CabECO ® or MIKROZON®. The availability and low cost of the technology are strong points for usage in poor areas of developing countries. Graphical abstract: Image 1 Highlights: A low-cost predisinfection treatment can be applied for surface and pore water. Softening and nitrate removal can be efficiently attained with PREDICO. Efficient connection with commercial electrolysers is attained for disinfection. Successful treatment for flow rates up to 300 L h −1 per PREDICO column is achieved.